Dysglycemia With Impaired Insulin Secretion After Resection of a High-Molecular-Weight IGF-II–Producing Tumor. Issue 1 (29th November 2022) - Shimada, Yasuho; Yamashita, Koh; Fukuda, Izumi; Aizawa, Toru
Abstract: Analysis of insulin and related glucoregulatory hormone secretion following high-molecular-weight insulin-like growth factor II (HMW-IGF-II)–releasing tumor excision has never been reported. In a man with chronic hypoglycemia—plasma glucose (PG), 2.1 mmol/L with undetectable serum insulin, less than 7.2 pmol/L on admission—the cause of the hypoglycemia was HMW-IGF-II in the serum secreted by an intrathoracic benign pleural solitary fibrous tumor (size: 15 × 17 × 12 cm). Removal of the tumor nullified serum HMW-IGF-II and hypoglycemia. Postoperative glucose metabolism was evaluated day 272 by 75 g oral glucose tolerance test (OGTT) and on days 5, 202, and 990 by fasted sampling. Glycated hemoglobin A1c (HbA1c ) was 37 to 41 mmol/mol, fasting PG was 5.3 to 5.4 mmol/L, and 2-hour PG at 75 g OGTT was 6.9 mmol/L, indicating that he was at the prediabetes stage. Homeostasis Model Assessment 2 of Insulin Resistance and Homeostasis Model Assessment 2 of β-Cell levels were within the normal range but the Stumvoll first phase was lowered. Insulin sensitivity and secretion were compared to age-, sex-, and body mass index–matched controls with normal glucose metabolism. Long-term HMW-IGF-II exposure of pancreatic islet β cells caused the functional impairment, that is, suppressed glucose-stimulated insulin secretion (GSIS), leading to nondiabetic hyperglycemia. This fact suggests long-term HMW-IGF-II exposure of the islet β cell specifically dampens GSIS.